Pathological investigation on pneumonia in goats in elazığ - Nursal Metin; Harun Özer; M. Kemal Çiftçi (Eurasian Journal of Veterinary Sciences)
Lungs taken from goats were examined for pneumonia. Macroscopically , pneumonia was found in 66 of 2784 lungs. It was recognized fibrinous pneumonia in 28 lungs (42 %), catarrhal-purulent bronchopneumonia in 15 lungs (23 %), interstitiel pneumonia in 14 lungs (22 %), verminous pneumonia in 8 lungs (12 %), also pulmonary adenomatosis was found in a case (1 %). This is a first report in goats in Turkey.